ANALISIS PENERIMAAN PAJAK DAERAH DAN RETRIBUSI DAERAH TERHADAP PENDAPATAN ASLI DAERAH KOTA BATAM - Wijaya, William; Yando, Agus Defri (LPPM Universitas Putera Batam, 2021)
Every region are required to be able to manage their respective region due to regional autonomy in Indonesia. Local tax and retribution play an important role in the management of a region because each region needs funds to manage their region. The Community is expected to increase their knowledge and fulfill their obligation to pay local tax and retribution. This study aims to analyze the effect of local tax revenue and retribution on regional income of Batam City. This study is quantitative research. Data obtained by documentation and using secondary data. The data is processed through the SPSS Version 25 Program. The result of this study showed that local tax (X1) has a significant effect on regional income. Reginal retribution (X2) has a significant effect on regional income. Both local tax and retribution have a significant effect on regional income of Batam City.